2012
DOI: 10.1371/journal.pone.0049959
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved C-Terminal Domain of the Aspergillus fumigatus Developmental Regulator MedA Is Required for Nuclear Localization, Adhesion and Virulence

Abstract: MedA is a developmental regulator that is conserved in the genome of most filamentous fungi. In the pathogenic fungus Aspergillus fumigatus MedA regulates conidiogenesis, adherence to host cells, and pathogenicity. The mechanism by which MedA governs these phenotypes remains unknown. Although the nuclear import of MedA orthologues has been reported in other fungi, no nuclear localization signal, DNA-binding domain or other conserved motifs have been identified within MedA. In this work, we performed a deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Adhesion implies that the fungus recognizes ligands on the surface of the host cell or a component of the ECM. The adhesion mechanism has been extensively studied in bacteria and pathogenic fungi (de Groot et al, 2013 ), such as Candida albicans (Nobile et al, 2008 ; Murciano et al, 2012 ; Puri et al, 2014 ; Silva et al, 2014 ; Formosa et al, 2015 ), Aspergillus fumigatus (Upadhyay et al, 2009 ; Al Abdallah et al, 2012 ; Xu et al, 2012 ; Zhao et al, 2012 ), Sporothrix schenckii (Ruiz-Baca et al, 2009 ; Teixeira et al, 2009b ; Sandoval-Bernal et al, 2011 ), Coccidioides immitis (Hung et al, 2002 ), Histoplasma capsulatum (Taylor et al, 2004 ; Suárez-Alvarez et al, 2010 ; Pitangui et al, 2012 ) and Penicillium marneffei (Srinoulprasert et al, 2006 , 2009 ; Lau et al, 2013 ). In a previous study, our group demonstrated that P. brasiliensis interacts with human fibronectin (Mendes-Giannini et al, 2006 ), which confirmed the results of the present study, although there was apparently greater adhesion to laminin.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion implies that the fungus recognizes ligands on the surface of the host cell or a component of the ECM. The adhesion mechanism has been extensively studied in bacteria and pathogenic fungi (de Groot et al, 2013 ), such as Candida albicans (Nobile et al, 2008 ; Murciano et al, 2012 ; Puri et al, 2014 ; Silva et al, 2014 ; Formosa et al, 2015 ), Aspergillus fumigatus (Upadhyay et al, 2009 ; Al Abdallah et al, 2012 ; Xu et al, 2012 ; Zhao et al, 2012 ), Sporothrix schenckii (Ruiz-Baca et al, 2009 ; Teixeira et al, 2009b ; Sandoval-Bernal et al, 2011 ), Coccidioides immitis (Hung et al, 2002 ), Histoplasma capsulatum (Taylor et al, 2004 ; Suárez-Alvarez et al, 2010 ; Pitangui et al, 2012 ) and Penicillium marneffei (Srinoulprasert et al, 2006 , 2009 ; Lau et al, 2013 ). In a previous study, our group demonstrated that P. brasiliensis interacts with human fibronectin (Mendes-Giannini et al, 2006 ), which confirmed the results of the present study, although there was apparently greater adhesion to laminin.…”
Section: Discussionmentioning
confidence: 99%
“…This PCR fragment was then cloned into the pGFP plasmid, as described previously, and digested with NcoI and NotI (28,29). The resulting plasmid, designated puge3-GFP, was used to transform wild-type A. fumigatus Af293 as described previously (30).…”
Section: Molecular and Genetic Manipulationsmentioning
confidence: 99%
“…1). For two of these proteins, MedA and LaeA, a functional role in transcriptional regulation has been defined experimentally [22][23][24] . We were unable to identify any functional domains in the orthologue of the TFIIIC subunit tfc6 or three proteins annotated as RfeD, F and G. Unlike in the model yeast, Saccharomyces cerevisiae, gene replacement strategies in A. fumigatus are complicated by relatively low levels of homologous recombination.…”
Section: Resultsmentioning
confidence: 99%